Language Acquisition: The Importance of Reading (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article aims to explore the significance of reading in language acquisition. Story-Reading and Free Voluntary Reading approaches are discussed in this article.